Le Divorce Des Pasteurs En Milieu Evangelique Ivoirien : Approche Socio-Anthropologique D’un Phenomene Desintegrateur A Travers Le Cas Des Communautes « Assemblees De Dieu » Et « Ministere International De La Revelation » De Yopougon, Abidjan, Côte-d’Ivoire - Patrice, N’dri Kouadio (European Scientific Journal, ESJ, 2017)
In evangelical communities, divorce is prohibited and a pastor is seen as a model, a spiritual guide and, above all, a guarantor of the Christian faith and morality. From this point of view, the breakdown of the marriage bond of a pastor with his wife undermines the cohesion and stability of the communities under his tutelage. This is because divorce is considered in Christian circles as a transgressive and anomic act. This article is a comprehensive approach of the divorce of pastors. It also shows its explanatory factors using a case study of two localities, the Assemblies of God Church and the International Ministry of the Revelation of Yopougon. The study was carried out using a socio-anthropological approach combined with both qualitative and quantitative methods. Based on the result of this study, the divorce of pastors is explained by several factors. The most essential include: the tensions and the recurring disputes in the couple; the continued infidelity of the spouses; the lack of forgiveness and reciprocal acceptance of spouses in case of error; the subtle flight of one of the spouses of the household, and so on. Although they are human guides and shepherds, pastors who have succumbed to these situations have destroyed the sacred bond of their marriage. These kinds of behavior of the evangelical guides have led to the regression of the social and political functioning of the Christian communities. Divorce, however, has become a symbolic act of destruction of socio-religious bonds while tarnishing the image of the evangelical world.